2014
DOI: 10.1007/s10886-014-0485-2
|View full text |Cite
|
Sign up to set email alerts
|

Similar Differentiation Patterns Between PBP Expression Levels and Pheromone Component Ratios in Two Populations of Sesamia nonagrioides

Abstract: Pheromone-binding proteins (PBPs) are thought to contribute to the specificity of the pheromone detection system through an initial selective binding with pheromone molecules. Here, we report different expression levels of PBP transcripts in the antennae of two populations of the stemborer Sesamia nonagrioides (Lepidoptera: Noctuidae), one collected in Europe and one in sub-Saharan Africa. The three PBP transcripts previously identified in this species were found to be expressed in both male and female antenna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The three homologous PBPs in the sibling species S. littoralis were also identified 40 , but the comparative analysis of their expression in male antennae was not reported, but we can suspect that the qualitative differences of the sex pheromone components and the three PBPs expressed in male antennae are important factors that permit correct mate recognition and sexual isolation in the two sibling species. This hypothesis was supported by a recently research, inverted expression ratio of PBP1 and PBP2 was found in two different geographical species of the stem borer Sesamia nonagrioides (Lepidoptera:Noctuidae), and this inverted expression ratio of PBP1 and PBP2 are correlated with the inverted ratio of their two sex pheromone components Z11-16:OH and Z11-16:Ald 49 . In addition, the three PBPs in S. littoralis were also expressed in the sensilla of the larvae antennae and suspected to be involved in foraging activity 50 .…”
Section: Discussionsupporting
confidence: 63%
“…The three homologous PBPs in the sibling species S. littoralis were also identified 40 , but the comparative analysis of their expression in male antennae was not reported, but we can suspect that the qualitative differences of the sex pheromone components and the three PBPs expressed in male antennae are important factors that permit correct mate recognition and sexual isolation in the two sibling species. This hypothesis was supported by a recently research, inverted expression ratio of PBP1 and PBP2 was found in two different geographical species of the stem borer Sesamia nonagrioides (Lepidoptera:Noctuidae), and this inverted expression ratio of PBP1 and PBP2 are correlated with the inverted ratio of their two sex pheromone components Z11-16:OH and Z11-16:Ald 49 . In addition, the three PBPs in S. littoralis were also expressed in the sensilla of the larvae antennae and suspected to be involved in foraging activity 50 .…”
Section: Discussionsupporting
confidence: 63%
“…The variation in the main compound differentiation within Alpinobombus taxa could be due to a switching off and on of specific metabolic pathways (Glaser et al 2014) and or by activation of an enzyme transcript present in a common ancestor (Roelofs et al, 2002). For instance, between CLGS of B. hyperboreus and B. neoboreus (two closely related species), the difference in the main compounds lays in the position of the C=C double bond (octadec-11-en-1-ol vs octadec-9-en-1-ol).…”
Section: Evolution Of Clgs In Alpinobombusmentioning
confidence: 99%
“…We already reported the presence of PBAN transcripts in the head and thoracic complex of Maruca vitrata , but absent in abdomen (Chang & Ramasamy, ). The PBP transcripts were mostly expressed in antennae, as evidenced in S. nonagrioides (Glaser et al ., ). There was one isoform cluster identified as a putative PBAN gene, and two isoform clusters were homologous to PBAN‐R (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…For instance, PBAN transcripts were present in the head and thoracic complex of legume pod borer ( Maruca vitrata ), a Crambid species (Chang & Ramasamy, ). The three PBP transcripts in the stem borer, Sesamia nonagrioides were found to be expressed in antennae (Glaser et al ., ). Hence, we focused on transcripts of S. recurvalis in the head (with antennae) and thoracic complex using Illumina sequencing technology.…”
Section: Introductionmentioning
confidence: 97%